Investigation of Death Rate due to Type 2 Traffic Accidents and Non-Traffic Accidents in Iran during 2013-2018 - Jalil Hasani; Saeed Erfanpoor; Seyed Saeed Hashemi Nazari (Tehran University of Medical Sciences, 2022)
Background: In the classification of road accidents, type 2 traffic accidents and non-traffic accidents are not considered and in Iran so far no special study has been done in the field of type 2 traffic accidents and non-traffic accidents, so we aimed to investigate the incidence of type 2 traffic accidents and non-traffic accidents in Iran. Methods: This cross-sectional was conducted on all individuals referred to Forensic Medicine Organization (FMO) from all over Iran who suffered from non-traffic accidents and type 2 traffic accidents during 2013-2018. Demographic information, accident information and other information including the location of the impact, the final cause of death and the date of the accident were examined. The information received from the FMO was first checked and then analyzed using Stata 11 statistical software. Results: During the 6-year study period, 10882 people lost their lives in type 2 traffic accidents (4779 people) and non-traffic accidents (5287 people). In terms of age, the highest incidence of type 2 traffic accidents and non-traffic accidents was observed in the age group over 65 years. The incidence of type 2 traffic accidents has not been increasing, while the trend of non-traffic accidents has been increasing. Conclusion: With respect to the high rate of deaths due to traffic accidents, including type 2 traffic accidents and non-traffic accidents, it is necessary for the national media and relevant agencies to educate the people about first aid and also inform about free relief services, timely presence is important.